Keterlibatan Masyarakat dalam Isu Lingkungan Kasus Tambang Emas di Banyuwangi - Khansa Nabilla Lutfiyah; Titania, Rahma; Dita Aprilia (CV. Kurnia Grup, 2024)
This study aims to examine the environmental and social impacts caused by gold mining activities in Banyuwangi, as well as the role of the community in the management of natural resources related to mining. The method used is a qualitative approach with in-depth interviews with local communities, government, and mining companies, as well as documentary analysis. The results show that gold mining in Banyuwangi has caused significant environmental damage, including water pollution, ecosystem destruction, and land degradation. Moreover, the social impact is the community's economic dependence on mining, which leads to changes in lifestyle and social inequality. The involvement of the community in environmental management is limited, with participation mainly focused on socio-economic aspects without considering long-term environmental sustainability. This study suggests that mining policies in Banyuwangi should be more inclusive by involving the community at every stage of planning and natural resource management. This is expected to reduce the negative impacts of mining on the environment and improve the sustainability of natural resources in the area.